Cerium oxide nanoparticle elicits oxidative stress, endocrine imbalance and lowers sperm characteristics in testes of balb/c mice. (21st November 2017) - Adebayo, O. A.; Akinloye, O.; Adaramoye, O. A.
Summary: The toxicity of metallic nanoparticles is a growing concern due to its application in industries and homes. We investigated the toxicity of cerium oxide nanoparticles (CeO2 NPs) on reproductive system in male balb/c mice. Twenty mice were divided into four groups of five animals each and treated thus: normal saline (control), 100, 200 and 300 μg/kg CeO2 NPs (i.p., ) thrice in a week for five consecutive weeks. Results showed that CeO2 NPs significantly reduced the levels of haemoglobin, PCV and RBC count relative to controls. In addition, luteinising and follicle‐stimulating hormones (FSH and LH) and prolactin were significantly reduced in the mice. Specifically, CeO2 NPs at 100 μg/kg decreased testosterone by 23%, while CeO2 NPs at 200 μg/kg decreased FSH, LH and prolactin by 25%, 26% and 13%, respectively. Testicular malondialdehyde was increased by 103%, 106% and 135% in mice treated with 100, 200 and 300 μg/kg CeO2 NPs, respectively. CeO2 NPs caused a significant reduction in activities of antioxidant enzymes and levels of reduced glutathione and total nitric oxide. Moreso, CeO2 NPs decreased sperm motility and count and increased total sperm abnormality in mice. Histology revealed congestion and degeneration of seminiferous tubules. Overall, CeO2 NPs induces testicular dysfunction via disruption of antioxidant/oxidant balance and endocrine suppression.